ANALISIS PENURUNAN RASA MUAL DAN MUTAH PADA IBU HAMIL DENGAN PENGGUNAAN INHALASI AROMA THERAPI LEMON DI SALAH SATU PUSKESMAS KABUPATEN BANDUNG - Mulyati, Iceu; Linda Rofiasari; Amirah Salwa Mainuha (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Pregnancy is a natural event that occurs in women. The average incidence of nausea and vomiting in 2019 was 67.9%. Where this incidence occurs in primigravida and multigravida pregnant women. Nausea and vomiting in medical parlance is called emesis. Emesis is a state of nausea that is sometimes accompanied by vomiting with a frequency of less than 5 times. Nausea and vomiting are caused by an increase in the HCG hormone. Nausea and vomiting can be overcome using pharmacological or non-pharmacological therapy, one of the non-pharmacological therapies is lemon aromatherapy. This study uses a descriptive type of research with a one group pre-test and post-test approach. The population used was 30 pregnant women who experienced nausea and vomiting at the Ibun Health Center in Bandung Regency in 2022 and the sample used was total sampling. The variable in this study is inhalation of lemon aromatherapy to reduce nausea and vomiting in pregnant women. The data used are primary data by conducting interviews using the PUQE-24 questionnaire research instrument. Data analysis in this study used univariate analysis. The results showed that the frequency before being given inhalation of lemon aromatherapy was that most experienced mild nausea and vomiting as many as 20 people (66.7%) and after being given inhalation of lemon aromatherapy most experienced mild nausea and vomiting as many as 17 people (56.7%). The average decrease before being given is 6.37 and after being given is 4.37. So that there is a decrease before and after being given lemon aromatherapy inhalation. Suggestions for health workers to be able to provide education regarding the provision of this alternative therapy to pregnant women who carry out examinations to overcome the nausea and vomiting.